Associations of Rsf-1 overexpression with poor therapeutic response and worse survival in patients with nasopharyngeal carcinoma. Issue 3 (12th November 2011) - Tai, Hui-Chun; Huang, Hsuan-Ying; Lee, Sung-Wei; Lin, Ching-Yih; Sheu, Ming-Jen; Chang, Shih-Lun; Wu, Li-Ching; Shiue, Yow-Ling; Wu, Wen-Ren; Lin, Chun-Mao; Li, Chien-Feng
Abstract : Aims: Deregulated chromatin remodelling often leads to aberrant gene expression in cells, thereby implicating tumour development and progression. As a subunit of remodelling and spacing factor complex, Rsf-1 (HBXAP), a novel nuclear protein with histone chaperon function, mediates ATPase-dependent chromatin remodelling and confers tumour aggressiveness in common carcinomas. However, the expression of Rsf-1 has never been reported in nasopharyngeal carcinoma (NPC). This study aimed at evaluating the expression status, associations with clincopathological variables and prognostic implications of Rsf-1 in a well-defined cohort of NPC. Methods: Rsf-1 immunoexpression was retrospectively assessed in biopsies of 108 consecutive NPC patients without initial distant metastasis and treated with consistent guidelines. The results were correlated with the clinicopathological features, therapeutic response, local recurrence-free survival (LRFS), distant metastasis-free survival (DMFS) and disease-specific survival (DSS). Results: Present in 49 cases (45%), Rsf-1 overexpression was associated with N2, 3 status (p=0.016), American Joint Committee on Cancer stage 3, 4 (p=0.004), and incomplete therapeutic response (p=0.041). In multivariate analyses, Rsf-1 overexpression not only emerged as the sole independent adverse prognosticator for LRFS (p=0.0002, RR 5.287) but also independently predicted worse DMFS (p=0.0011, RR 3.185) and DSS (p<0.0001, RR 4.442), along with T3, 4 (p=0.0454) and N2, 3 (p=0.0319), respectively. Conclusion: Rsf-1 overexpression is common and is associated with adverse prognosticators and therapeutic response, which confers tumour aggressiveness through chromatin remodelling, and represents a potential prognostic biomarker in NPC.